Experimental study on the magnetic pulse welding process of large aluminum tubes on steel rods. (February 2019) - Bellmann, J; Schettler, S; Dittrich, S; Lueg-Althoff, J; Schulze, S; Hahn, M; Beyer, E; Tekkaya, A E
Abstract: Solid state welding technologies enable dissimilar metal welding without critical intermetallic phase formation. Magnetic Pulse Welding (MPW) is a promising joining method for hybrid sheet connections in car body production or for manufacturing of dissimilar tube connections. Given a suitable MPW process design, the shear testing of MPW joints usually leads to failure in the weaker base material. This finding emphasizes the high strength level of the joining zone itself. Consequently, the transmission of higher forces or torques, respectively, requires stronger materials or adapted geometries. In the present experimental study, the diameter of an exemplary driveshaft was doubled to 80 mm at constant tube wall thickness to increase the load bearing capability. The characteristic impact flash was recorded at different positions around the tube's circumference and it was used to adjust the most relevant process parameters, i.e. working length and acceleration gap, at the lower process boundary. In metallographic analysis, the final shapes of both joining partners were compared with the original driveshaft dummies on macroscopic and microscopic scale. The typical wavy interface between aluminum and steel was analyzed in detail. Doubling the tube diameter lead to four times higher torque levels of failure during quasistatic and cyclic torsion tests.